Analysis of the Mediating Role of Customer Satisfaction in the Influence of Service Quality and Facilities on Word of Mouth at TK Intan Surabaya - Wiratama, Alif Kurniawan; Mujanah, Siti; Fianto, Achmad Yanu Alif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine and analyze the effect of service quality and facilities on word of mouth through customer satisfaction as a mediating variable at INTAN Surabaya Kindergarten. The sampling technique used was a saturated sample, with a total of 98 respondents. Data collection is done through distributing questionnaires that have been tested for validity and reliability to ensure data accuracy and consistency. Data analysis was carried out using SmartPLS version 4 software. This study tests the hypothesis using the Structural Equation Model (SEM) with the Partial Least Square (PLS) analysis method. The measurement scale in this study uses a Likert scale. The results of the study explain that service quality has a negative and insignificant effect on word of mouth, facilities have a positive and significant effect on word of mouth, service quality has a positive and significant effect on customer satisfaction, facilities have a positive and significant effect on customer satisfaction, satisfaction has a positive and significant effect on word of mouth, customer satisfaction is able to mediate the effect of service quality on word of mouth, and customer satisfaction is able to mediate the effect of facilities on word of mouth.